An alternative Candida spp. cell wall disruption method using a basic sorbitol lysis buffer and glass beads - Lim, Crystale Siew Ying; Tung, Chee Hong; Rosli, Rozita; Chong, Pei Pei (Elsevier, 2008)
This report describes a modified, cost-effective method of cell wall disruption for the yeast Candida spp., which employs the use of glass beads in a simple sorbitol lysis buffer. This method can be used in conjunction with a commercial RNA or genomic DNA isolation method to obtain high-quality RNA or DNA.